(untitled) (Research, Society and Development, 2024)
Objective: To present studies that deal with pharmaceutical services and their effectiveness in treating patients with Diabetes mellitus. Method: Integrative review. Results: It was observed that there are different strategies to improve the quality of pharmaceutical care for diabetic patients, including telemedicine through SMS reminders, telephone calls and applications that provide support for self-care and/or self-management. Conclusion: It is recognized that the pharmaceutical professional is important for health care, through the provision of pharmaceutical services that apply pharmaceutical care as a strategy to promote a better quality of life for diabetic patients.